CHARACTER CONFLICTS IN THE NOVEL CINTA ANAK KARAENGBY AHMAD SAHIDE - Saira; La Ode Balawa; La Yani Konisi (Jurnal Casa Cendekia, 2026)
This study aims to describe the forms of character conflict in the novel Cinta Anak Karaeng by Ahmad Sahide. The research employed a qualitative descriptive method with a literary psychology approach. The data were obtained through library research, with the novel serving as the primary data source and supported by relevant scholarly articles and journals. Data collection was conducted using close reading and note-taking techniques, while data analysis involved data reduction, classification, interpretation, and conclusion drawing. The findings indicate that character conflict in the novel consists of internal and external conflicts. Internal conflicts are experienced mainly by the characters Karaeng Asmi and Daro in the form of psychological struggles, emotional dilemmas, fear, and anxiety caused by contradictions between personal desires and rigid traditional norms. External conflicts arise from confrontation between individual characters and family authority as well as social traditions that enforce caste-based stratification. The study reveals that internal and external conflicts are closely interconnected, with social pressure intensifying psychological turmoil. These conflicts reflect broader socio-cultural realities within the Karaeng community and demonstrate how tradition functions as both cultural identity and an instrument of social control. This study contributes to Indonesian literary studies by highlighting the significance of character conflict in novels rooted in local cultural contexts.